The correlation of chest X-ray characteristics and severity scores with clinical outcomes in COVID-19 pneumonia patients - Sukpairoh, Supawan; Phuntanasiri, Supharat; Songthamwat, Metha; Sunthorn, Thatsanee (Journal of Medicine and Health Sciences, 2022)
Abstract The newly emerging coronavirus disease (COVID-19) causes pneumonia. This retrospective descriptive study aims to evaluate the correlation of chest X-ray (CXR) characteristics and severity scores with clinical outcomes in moderate and severe COVID-19 pneumonia patients who require supplemental oxygen, between January 1st, 2021, and December 31st, 2021. The Spearman's correlation coefficient analysis was performed for statistical analysis. There was a total of 305 patients, 64.26% were discharged, and 24.26% died. The mean age was higher in severe than in moderate groups (58.43 and 52.88 years old; p=0.009). The median length of supplemental oxygen and hospital stay were significantly higher in severe rather than moderate groups (10 and 4, and 16 and 12 days, respectively; p<0.001). Peripheral ground-glass opacity in the lower zones of the lungs was the most common finding. Consolidation, perihilar distribution, and diffuse involvement are associated with increased severity, particularly the highest CXR (p<0.001). The severity scores of the initial and highest CXR were higher in the severe group compared to the moderate group. RALE score of the initial CXR equal to or more than eight (adjusted RR = 1.18, 95% CI 1.07-1.31) and Brixia score equal to or more than seven (adjusted RR = 1.16, 95% CI 1.04-1.29) were associated with a higher risk of mortality. In conclusion, the initial and highest CXR characteristics and severity scores have prognostic utility in predicting severe COVID-19 pneumonia. The scores predicted mortality with optimal cut-off points of RALE score of the initial CXR equal to or more than eight or Brixia score equal to or more than seven.